Relativistic Theory - Năstase, Horaţiu [UNESP] (My University, 2019)
In this chapter, we re-derive, and extend, the analysis of the previous chapter within general relativity. We will re-derive the Friedmann equation from the relativistic treatment, of the FLRW metric, and then describe the various types of matter in detail, and the corresponding evolution of the Universe.